Mudanças nos parâmetros técnicos dos projetos de crédito rural: o caso dos projetos de assentamentos no sudeste do Pará - OLIVEIRA, Dvandro Pedro de (2005)
This work has the purpose of studying the occurred changes in the technical parameters, during the understood period from 1994 to 2004. This period was analyzed at two distinct moments: the first one studies the years from 1994 to 1999, which coincides with the predominance of the EMATER in the elaboration of the projects, and the second one studies the years from 2000, with the biggest participation of the lenders of service in the elaboration of projects for settled familiar agriculturists. This second moment coincides with the participation of the lenders of service of the Lumiar Project. The analysis privileges the second moment of changes in the technical parameters, which involved the participation of the familiar agriculturists and different institutions attached to the agricultural credit for settlements. The discussions about the projects were carried in the technical discussion forums (seminaries and meetings or workshops) promoted by the technical chamber. Through the improvement of the dialogue among the actors in the forums of technical discussions, the construction of the technical parameters in the Southeast of the state of Pará has been providing an improvement in the application of the credit, although there is still a lack of a more systemized analysis about the projects adaptation, in the agricultural establishments. The absence of regional technical indices may put some projects at risk, as the financing of the Forest PRONAF. The main technical advance in the discussions of the credit for the familiar agriculture was the incorporation of the activities regarding to small and medium animals and to agroflorestais systems (SAF’s), as financed items which allowed a bigger adaptability of the credit to the reality of the familiar agriculturists.